Symbiont polyphyly, co-evolution, and necessity in pentatomid stinkbugs from Costa Rica - Bistolas, Kalia S. I.; Sakamoto, Reid I.; Fernandes, José A. M.; Goffredi, Shana K. (Frontiers in Microbiology, 2014)
Interdomain symbioses with bacteria allow insects to take advantage of underutilized niches and provide the foundation for their evolutionary success in neotropical ecosystems. The gut microbiota of 13 micro-allopatric tropical pentatomid species, from a Costa Rican lowland rainforest, was characterized and compared with insect and host plant phylogenies. Like other families within the Pentatomomorpha, these insects (within seven genera - Antiteuchus, Arvelius, Edessa, Euschistus, Loxa, Mormidea and Sibaria) house near-monocultures of gamma-proteobacteria in modified midgut crypts, comprising three distinct lineages within the family Enterobacteriaceae. Identity of the dominant bacteria (78-100% of the recovered 16S rRNA genes) was partially congruent with insect phylogeny, at the level of subfamily and tribe, with bacteria closely related to Erwinia observed in six species of the subfamily Pentatominae, and bacteria bacteria in a novel clade of Enterobacteriaceae for seven species within the subfamilies Edessinae and Discocephalinae. Symbiont replacement (i.e. bacterial ‘contamination’ from the environment) is probable due to modified maternal transmission by smearing of bacteria onto the egg surfaces during oviposition. This strategy was confirmed for Sibaria englemani, and suspected for four species from two subfamilies, based on observed probing of eggs by nymphs in captivity. Symbiont-deprived S. englemani, acquired via egg surface sterilization, exhibited significantly extended second stadia (9.1 days compared with 7.9 days for symbiotic nymphs; p=0.0001, Wilcoxon’s rank with Bonferroni correction), slower linearized growth rates (p=0.005, Welch 2-sample t-test), and observable differences in ceca morphology compared to symbiotic nymphs. Combined, these results suggest a role of the symbiont in host development, the reliable transference of symbionts via egg surfaces, and a degree of co-speciation between symbiont and tropical pentatomid host insects.